Methods of Testing of Individual Auditing Tasks by External Quality Controllers - VADIM YA. Ovsiychuk; VALENTINA V. Ovsiychuk; YURY A. Trusov (Учёт. Анализ. Аудит)
The article describes the sampling techniques to verify the quality of performance of auditing tasks and duties, among which it is advisable to use non-statistical and varied sampling methods. During the selection of the tasks for sampling methods, the following benchmarks can be chosen as the example: groups of the auditors of an organization; specialization of the entities that undergo the auditory check up; the type of service rendered; the cost of auditing tasks. When analyzing the selected sample of aggregate concept and design it is necessary to take into account the specifics of the auditing quality control activities. Its main idea is the fact that, unlike auditing, inspection methods are of a more formal approach. Exploring the working papers of auditors, quality controllers use one of the methods of quality control of auditors - the inspection of the automation of the planning process for each specific task. During the test, the external quality controllers assess the level of automation of the work of the auditors. You can use different approaches to this assessment, for example, the introduction of a three-point scale computerization of the work of the auditors. For external supervisors it is important to check the quality of the auditing plan and the auditing program of an organization. The described methods of quality control of the individual planning of auditing tasks ensure at least the minimum confidence in the effectiveness of such planning.